Regulatory roles of alternative splicing at Ezh2 gene in mouse oocytes - Shi-meng Guo; Xing-ping Liu; Qing Tian; Cai-feng Fei; Yi-ran Zhang; Zhi-ming Li; Ying Yin; Ximiao He; Li-quan Zhou (Reproductive Biology and Endocrinology, 2022)
Abstract Background Enhancer of zeste homologue 2 (EZH2), the core member of polycomb repressive complex 2 (PRC2), has multiple splicing modes and performs various physiological functions. However, function and mechanism of alternative splicing at Ezh2 exon 3 in reproduction are unknown. Methods We generated Ezh2 Long and Ezh2 Short mouse models with different point mutations at the Ezh2 exon 3 alternative splicing site, and each mutant mouse model expressed either the long or the short isoform of Ezh2. We examined mutant mouse fertility and oocyte development to assess the function of Ezh2 alternative splicing at exon 3 in the reproductive system. Results We found that Ezh2 Long female mice had normal fertility. However, Ezh2 Short female mice had significantly decreased fertility and obstructed oogenesis, with compromised mitochondrial function in Ezh2 Short oocytes. Interestingly, increased EZH2 protein abundance and accumulated H3K27me3 were observed in Ezh2 Short oocytes. Conclusions Our results demonstrate that correct Ezh2 alternative splicing at exon 3 is important for mouse oogenesis.